"Blue Ribbon" Commissions, Interest Groups, and the Formulation of Policy in the American States. Issue 1 (5th December 2014) - Ritchey, Mark; Nicholson‐Crotty, Sean
<x xml:space="preserve">Abstract</x> Despite the prevalence of state‐level commissions convened to make policy recommendations, research to date has not systematically investigated the ways in which these bodies impact policy or degree to which state‐level interest groups can use these institutions in that process. We argue that less powerful groups will favor these mechanisms and use them to get issues onto the institutional agenda and to increase the likelihood of legislative success. We also suggest that traditionally powerful groups will oppose the creation of reform‐minded task forces, but will likely use them to hinder policy change once they are formed. We test this assertion in an analysis of the creation and recommendations of task forces convened to study autism insurance mandates, as well as the eventual adoption of such mandates, in the American states between 2001 and 2010. The results suggest that public and industry groups influence the formation and recommendations of task forces, but that the latter appears to have a relatively larger impact. They also suggest that a task force recommendation has a large impact on the likelihood of adopting an autism insurance mandate and that neither the insurance industry nor autism advocacy groups have a direct influence on adoption after controlling for the presence of a recommendation.